Structural and Semantic Analysis of Kivertsy District of Volyn Region Residents’ Surnames (Linguostylistic Studies, 2018)
The article analyzes surnames recorded in 12 villages of the Kivertsi district, Volyn region.The name-creating word (stem) prearranges the division of surnames into lexical-semantic groups, including the main source of their creation. Accordingly, the study has revealed proper personal names, names of persons by the origin and place of residence, names of persons by the social status or occupation, names of persons by their individual features.Nominal surnames predominantly reflect lexical-semantic and morphological ways of creation. This group considers surnames that correspond to full personal names (Sydor, Yakym, Zhdan), coincide with the stems of the abridged/shortened forms of names (Kost', Krat, Fen’), coincide with the stems of abridged-suffixated names (Gryn', Antos', Dorosh), and correspond to diminutive/affectionate or rude forms of names (Yevtushko, Motrunchyk, Petryna). In the group of morphological formations, surnames with patronymic (Khomych, Kharkevych, Maryniak) and possessive suffixes (Hnativ, Hrytsyshyn) prevail. Among the surnames that indicate the origin or place of residence of the family founder, there are anthroponyms that name the nationality of the ancestor (Voloshyn, Voloshchuk, Lytvyn), indicate belonging to ancient nationalities and dialect groups (Hotsuliak, Mazur), generally indicate the place of residence (Zavgorodny, Nagorny), name a particular location (Baletskyi, Kozynets, Ostrovchuk).The article analyzes the surnames that indicate the social affiliation or occupation of the bearers. Such surnames indicate the class stratification of society (Bohatko, Holets); administrative positions (Voitovych, Yemets); woodworking crafts (Bondar, Kolodiy Mazhar); cooking and food pocessing (Molochnyk, Oliinyk, Pekar); weaving, tailoring, shoemaking (Shapoval, Shvets), making household items (Lynnyk, Kotliar); agriculture (Budnyk, Kozyarchuk, Ogorodnik); building (Hontar, Muliar); trade (Kachmar, Kramar, Chumak), indicate other professions and trades (Voskoboynik, Dekhtiaruk, Zvarych).Surnames formed on the basis of the bearers' individual characteristics indicate their physical, mental traits, intellectual level, and behavior features (Hlushko, Kryvyi, Dziuba; Svystun, Struts, Tsymbaliukta, and others).The revealed and analyzed surnames preserve information about various historical and socio-economic processes in the life of the Ukrainian people for the descendants.
Keywords: anthroponym; surname; personal names; lexical-semantic groups